A production transfer procedure based on risk management principles. (18th February 2019) - Mogos, Maria Flavia; Fredriksson, Anna; Alfnes, Erlend
Abstract : Purpose: This paper aims to develop a procedure for preparing production transfers based on risk management principles. The procedure should help companies reduce the amount of supply chain disruptions during transfers and achieve their outsourcing/offshoring objectives. Design/methodology/approach: The procedure was developed during a three-year Design Science study. First, a literature review and case studies were conducted to frame the research problem. Second, a preliminary procedure was developed based on preventive risk mitigation actions from the production transfer literature. Third, the procedure was implemented during an electronics-offshoring case and refined during workshops with the sender and receiver's transfer personnel. Fourth, during a seminar, transfer practitioners verified the procedure by applying it to outsourcing/offshoring cases with which they had experience. Findings: Most of the preventive actions were evaluated as relevant for the transfers the procedure was applied to, regardless of industry and relocation type. Moreover, the electronics-offshoring case showed that the success of a production transfer not only depends on the physical, knowledge and supply chain transfers, as presented in earlier research, but also on the administrative transfer and on the organisation, project and quality management actions. This paper also attempts to enhance the production transfer literature by clarifying transfer risk management. Practical implications: The procedure can be used during the production transfer phase as a preparation procedure. Moreover, it informs the decision-making process during the relocation-decision and supplier-selection phases. Originality/value: To the authors' knowledge, this is the first production-transfer-preparation procedure based on risk management principles.